PROMOTING “EDUCATION FOR ALL” IN INCLUSIVE EDUCATION TO PRIMARY EDUCATION STUDENTS - Nurmamatov Abduqodir Abduxhor o‘g‘li, (Лучшие интеллектуальные исследования, 2024)
Abstract: The article focuses on the issues of education of children with disabilities in the general education system. Promotion of “Education for All” to primary school students. Classification of the principles of goals and objectives of inclusive education and the basics of inclusive education are described.